2018
DOI: 10.1111/epi.14444
|View full text |Cite
|
Sign up to set email alerts
|

Psychological treatments for adults and children with epilepsy: Evidence‐based recommendations by the International League Against Epilepsy Psychology Task Force

Abstract: Given the significant impact that psychosocial factors and epilepsy treatments can have on the health-related quality of life (HRQOL) of individuals with epilepsy and their families, there is great clinical interest in the role of psychological evaluation and treatments to improve HRQOL and comorbidities. Therefore, the International League Against Epilepsy (ILAE) charged the Psychology Task Force with the development of recommendations for clinical care based on evaluation of the evidence from their recent Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 144 publications
(408 reference statements)
3
78
0
3
Order By: Relevance
“…According to the National Institute for Clinical Excellence (NICE), psychological therapies represent first line treatment for mild to moderate depression in both the general population [72] and in subjects with a chronic health problem [73]. Data in people with epilepsy are still limited but systematic reviews and meta-analysis have shown that psychological therapies are associated with a significant improvement in quality of life [74,75] and a recent document from the ILAE Psychology Task Force confirmed that psychotherapeutic interventions are recommended in patients with epilepsy and mild to moderate depression, even if the level of evidence is still moderate and further studies are needed [76].…”
Section: Psychological Treatmentsmentioning
confidence: 99%
“…According to the National Institute for Clinical Excellence (NICE), psychological therapies represent first line treatment for mild to moderate depression in both the general population [72] and in subjects with a chronic health problem [73]. Data in people with epilepsy are still limited but systematic reviews and meta-analysis have shown that psychological therapies are associated with a significant improvement in quality of life [74,75] and a recent document from the ILAE Psychology Task Force confirmed that psychotherapeutic interventions are recommended in patients with epilepsy and mild to moderate depression, even if the level of evidence is still moderate and further studies are needed [76].…”
Section: Psychological Treatmentsmentioning
confidence: 99%
“…A key clinical implication is the potential utility of self‐management intervention to advance care for depressed people with epilepsy. A recent literature review found that psychological treatments that encompass a broad range of nonpharmacological interventions for individuals, families, or groups have strong evidence for improving depressive symptoms in epilepsy. However, this review only identified one study that specifically investigated depression outcomes for a self‐management intervention .…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] A recent literature review of psychological treatments in people with epilepsy found that one-third of patients receiving cognitive behavioral therapy (CBT) interventions, compared to 10% of controls, could be considered "reliably improved." 16 However, given the great number of undertreated people with epilepsy who also have depression, the development of additional psychological approaches, including alternatives to CBT, is warranted. There is considerable conceptual overlap among psychological approaches intended to help improve health outcomes among people with epilepsy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include improved identification of mental health needs, better access to evidencebased psychological treatment, provision of patient-centred care, avoiding fragmentation of health services, reducing stigma associated with mental health treatment, optimising both mental health and physical health outcomes and strengthening overall health systems (Patel et al 2013). Integration is needed as psychological interventions targeting the enhancement of health-related quality of life, medication adherence and comorbid mental health symptoms (for example anxiety, depression and disruptive behaviour) have been recommended as part of comprehensive epilepsy care (Michaelis et al 2018).…”
Section: Introductionmentioning
confidence: 99%